Taper of the Appendix and Lymphoid Distribution in the Zimbabwean Adult Male Population: A Cadaveric Study - Khan, Maimoona; Govo, Morris; Makosa, Tapera (Journal of Rawalpindi Medical College, 2024)
Objective: To determine the relationship between lymphoid distribution and taper of the vermiform appendix in the adult Zimbabwean male population. Study design: A cross-sectional descriptive study Place and duration of study: A six-month study carried out in the Anatomy Department (Gross Anatomy Laboratory), University of Zimbabwe, College of Health Sciences, Harare (from October 2021 to March 2022). Methods: A total of 15 male cadavers from the Department of Anatomy at the University of Zimbabwe were used. The length of the appendix, luminal diameter, external diameter and wall thickness were measured using a vernier calliper at three segmental levels, i.e. the base, mid part and the tip of the appendix. IBM SPSS version 23 was used to calculate the means and standard deviations. To determine the lymphoid distribution, histological sections of the appendix were prepared and viewed using a light microscope. Results: Appendix length ranged from 4.52cm to 15cm with an average length and standard deviation of 8.43± 2.45cm. The average luminal diameter with standard deviation at the base, mid-part, and tip was found to be 0.53± 0.22cm, 0.39± 0.21cm and 0.36±0.17cm, respectively. The average external diameter with standard deviation at the base, mid-part and tip was measured as 0.74± 0.18cm, 0.61± 0.16cm and 0.55± 0.15cm, respectively. The average wall thickness with standard deviation at the base, mid-point and tip was noted to be 0.21± 0.14cm, 0.25± 0.14cm and 0.20± 0.17cm, respectively. In this study, the lymphoid follicles were found to be more extensive at the base and mid-part, and less extensive at the tip. The lymphoid follicles extended from the mucosa to the submucosa at the base and mid-part while at the tip they only traversed the mucosa. External diameter decreased from base to tip, showing the taper of the appendix in the adult male Zimbabwean population. Conclusion: It was found that a strong relationship exists among the lymphoid tissue aggregations, luminal diameter and wall thickness of the adult male Zimbabwean inhabitants. The luminal diameter was observed to decrease in cadavers having an increase in wall thickness or hypertrophy of the lymphoid tissue. Moreover, there was a reduction in the number and size of lymphoid follicles along the length of the appendix.